Embracing heterogeneity: Essays in entrepreneurship and human capital - Theodor Lucian Vladasel (Copenhagen Business School (CBS), 2019)
How does heterogeneity in individual and firm characteristics explain differences in occupational choice and organizational performance? This thesis considers variations in human capital profiles and organizational forms to provide insight into drivers of entrepreneurship entry, persistence, and income on the one hand, and the ability of social enterprises to motivate employee action on the other. Using econometric techniques and experimental approaches, the three essays that comprise this thesis provide novel insights into the determinants of different types of entrepreneurship and the human resource practices of social enterprises.
hdl:10398/9751
Keywords: 650; Entrepreneurship; Familienstruktur; Wirkungsanalyse; Sozialwirtschaft